ANALYSIS OF THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, AND FIRM SIZE ON FIRM VALUE IN PROPERTY AND REAL ESTATE COMPANY LISTED ON THE INDONESIA STOCK EXCHANGE 2020-2024 PERIOD - Farah Fauziah Firmansyah; Puji Astuti; Sigit Puji Winarko (JAT : Journal Of Accounting and Tax, 2025)
This study analyzes of the influence of Good Corporate Governance (GCG), Corporate Social Responsibility (CSR), and firm size on corporate value in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. Corporate value is measured using the Price to Book Value ratio. GCG is proxied by the proportion of independent commissioners, CSR based on the disclosure of the GRI Standards indicator, and firm size is measured by the natural logarithm of total assets. The study employs a quantitative approach with a causal research design and utilizes multiple linear regression. Secondary data were obtained from annual and sustainability reports. A total of 19 companies were selected through purposive sampling, resulting in 95 observations over a five-year period. Data analysis involved classical assumption testing followed by hypothesis testing using the t-test, F-test, and coefficient of determination. The findings reveal that GCG has a significant positive effect on corporate value, whereas CSR and firm size do not exhibit significant individual effects. However, simultaneously all three variables collectively have a significant impact on corporate value. These results provide valuable insights for corporate management and investors in making decisions regarding governance practices, social responsibility initiatives, and strategic asset development